2005
DOI: 10.1136/jmg.2005.040352
|View full text |Cite
|
Sign up to set email alerts
|

Genotype-phenotype correlation in Costello syndrome: HRAS mutation analysis in 43 cases

Abstract: Background: Costello syndrome (CS) is a rare multiple congenital abnormality syndrome, associated with failure to thrive and developmental delay. One of the more distinctive features in childhood is the development of facial warts, often nasolabial and in other moist body surfaces. Individuals with CS have an increased risk of malignancy, suggested to be about 17%. Recently, mutations in the HRAS gene on chromosome 11p13.3 have been found to cause CS. Methods: We report here the results of HRAS analysis in 43 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
204
0
4

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 214 publications
(220 citation statements)
references
References 19 publications
(21 reference statements)
10
204
0
4
Order By: Relevance
“…Phenotypic features of Costello syndrome include polyhydramnios, increased birth weight, feeding problems, failure to thrive, short stature, developmental delay, pleasant personality, characteristic facial appearance, soft skin, papillomata, spatulate fingerpads, deep palmar creases, joint and skin laxity, kyphoscoliosis, pectus, and splayed fingers with ulnar deviation. Since the discovery that HRAS gene mutations cause Costello syndrome [Aoki et al, 2005], at least 150 genotyped patients have been studied [reviews by Estep et al, 2006;Gripp et al, 2006;Kerr et al, 2006;Zampino et al, 2007]. Consensus expert opinion recommends that Costello syndrome be defined solely by HRAS mutations , which differs from the molecular heterogeneity of CFC syndrome and Noonan syndrome.…”
Section: Introductionmentioning
confidence: 99%
“…Phenotypic features of Costello syndrome include polyhydramnios, increased birth weight, feeding problems, failure to thrive, short stature, developmental delay, pleasant personality, characteristic facial appearance, soft skin, papillomata, spatulate fingerpads, deep palmar creases, joint and skin laxity, kyphoscoliosis, pectus, and splayed fingers with ulnar deviation. Since the discovery that HRAS gene mutations cause Costello syndrome [Aoki et al, 2005], at least 150 genotyped patients have been studied [reviews by Estep et al, 2006;Gripp et al, 2006;Kerr et al, 2006;Zampino et al, 2007]. Consensus expert opinion recommends that Costello syndrome be defined solely by HRAS mutations , which differs from the molecular heterogeneity of CFC syndrome and Noonan syndrome.…”
Section: Introductionmentioning
confidence: 99%
“…Of two CS patients with a p.K117R mutation, one patient had an atypical phenotype such as microretrognatism and slightly less-pronounced plantar and palmar creases. 7 The other patient had mild craniofacial manifestations of CS. 13 One patient with the p.A146V mutation showed a mildly coarse face and did not have deep palmar creases.…”
Section: Discussionmentioning
confidence: 98%
“…The number of fatal cases was 5/138 patients with p.G12S, 4/6 with p.G12C, 3/17 with p.G12A, 3/4 with p.G12D, 2/2 with p.G12V, 1/1 with p.G12E and 1/1 with p.E63K. 3,[5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] The mortality of patients with p.G12C or p.G12D was significantly higher than that of the patients with the more common p.G12S (P¼0.026 by Fisher's exact test). Previous studies have shown that the p.G12V substitution has the highest transformative potential (p.G12V4p.G12A, p.G12S, p.G12C, p.G12D4p.G13D) and is the most frequently found mutation in human tumors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations